Triarylmethanes, a New Class of Cx50 Inhibitors - BODENDIEK, SILKE; RUBINOS, CLIO; TRELLES, MARIA P.; JENKINS, DAVID; COLEMAN, NICHOLE; Wulff, Heike; SRINIVAS, MIDUTURU (Frontiers in Pharmacology, 2012)
The paucity of specific pharmacological agents has been a major impediment for delineating the roles of gap junction channels formed by connexin proteins in physiology and pathophysiology. Here, we used the selective optimization of side activities (SOSA) approach, which has led to the design of high affinity inhibitors of other ion channels, to identify a specific inhibitor for channels formed by Cx50, a connexin subtype that is expressed in the lens. We initially screened a library of common ion channel modulating pharmacophores for their inhibitory effects on Cx50 gap junction channels, and identified four new classes of compounds. The triarlymethane (TRAM) clotrimazole was the most potent Cx50 inhibitor and we therefore used it as a template to explore the structure activity relationship (SAR) of the TRAMs for Cx50 inhibition. We here describe the design of T122 (N-[(2-methoxyphenyl)diphenylmethyl]-1,3-thiazol-2-amine) and T136 (N-[(2-iodophenyl)diphenylmethyl]-1,3-thiazol-2-amine), which inhibit Cx50 with IC50s of 1.2 µM and 2.4 µM. Both exhibit at least 10-fold selectivity over other connexins as well as major neuronal and cardiac voltage-gated K+ and Na+ channels. The SAR studies also indicated that the TRAM pharmacophore required for connexin inhibition is significantly different from the pharmacophore required for blocking the calcium-activated KCa3.1 channel. Both T122 and T136 selectively inhibited Cx50 gap junction channels in lens epithelial cells, suggesting that they could be used to further explore the role of Cx50 in the lens. In addition, our results indicate that a similar approach may be used to find specific inhibitors of other connexin subtypes.